FACTORS OF SMALLHOLDERS COFFEE FARMERS’ IMPLEMENTATION IN DIVERSIFICATION POSTHARVEST IN JEMBER REGENCY - Sudarko Sudarko (UNEJ e-Proceeding, 2012)
Agricultural development aims to develop system of sustainable agriculture. Coffee agribusiness development must be full supported with post-harvest sectors. The aims of the research were (1) to identify the implementation of diversification post-harvest technology by smallholders coffee farmers (2) to analyze the factors of smallholders coffee farmers’ Capability of implementation diversification post-harvest. The research method used descriptive-correlation. The analysis of the data was performed by using the correlation test of Tau b Kendall. The method of the research used was a survey using 100 respondents from all of center smallholders coffee farmers in Jember Regency. The result showed that; (1) Capability level of smallholders coffee farmers were average level,(2) the factors of smallholders coffee farmers’ Capability of implementation diversification postharvest were internal factors of farmer’s characteristics and external factors of farmer’s characteristics.